DAMPAK MEDIA GAMBAR BERSERI TERHADAP PENINGKATAN KETERAMPILAN MENULIS CERITA - Hanriana, Vivi Evanti; Salim, Herli (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Writing is one of the Indonesian language skills that must be mastered by elementary school students. Writing is a place to be able to communicate between one person and another, writing skills cause students to think deeply, logically, systematically, and scientifically, thus affecting their learning outcomes. Students working and writing someone can express feelings and ideas. Students are expected to master four skills when learning Indonesian, namely: reading, writing, listening, and speaking. Complete the skills of essay writing does not come naturally or naturally, but still requires a repetitive, intensive process of practice and requires a time-consuming learning stage and a long process. Learning media has a very important role in the process of teaching and learning activities, in addition to efforts to achieve learning, learning media is also very useful in attracting attention and encouraging the student spirit to learn. The study aims to find out how the ether displays changes in narrative writing after using serial visual media. The method used in this research is a qualitative approach with class action research. This study uses data collection methods in the form of periodic tests. The results of this study are factors that can increase the skill of making a student's story based on good and appropriate indicators of writing skills. In 3 cycles, students' writing skills increased by a percentage of 32%, increased by 57%, then increased by 84%. Through the use of these sequences of images, it is seen that students' narrative writing skills improve. Not only that, students are also trained to write narratives because this process is done over and over again to improve student narrative results.